STRATEGI PEMBELAJARAN GURU PENGGERAK DALAM MEWUJUDKAN KEPEMIMPINAN PESERTA DIDIK (STUDENT AGENCY) DI SDN TANJUNGSARI - Islamiah, Nurul; Syachruroji, A.; Hatima, Yoma (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
In the Merdeka Curriculum era, elementary education positions teachers as facilitators and instructional leaders who encourage active student participation (student agency). This study aimed to describe the learning strategies implemented by a Guru Penggerak at SDN Tanjungsari in fostering student leadership. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation involving the *Guru Penggerak*, the principal, and fifth-grade students. The findings revealed that the teacher implemented student-centered learning by emphasizing three key aspects: voice, choice, and ownership. Students were given opportunities to express their opinions, choose their learning approaches, and take responsibility for their learning outcomes. These strategies contributed to increased independence, self-confidence, and active engagement among students in the classroom. In conclusion, the *Guru Penggerak* plays a significant role in fostering student leadership through participatory and reflective learning practices.